Starch-Based Hydrogels as a Drug Delivery System in Biomedical Applications - Chung-Sung Lee; Hee Sook Hwang (Gels, 2023)
Starch-based hydrogels have gained significant attention in biomedical applications as a type of drug delivery system due to their biocompatibility, biodegradability, and ability to absorb and release drugs. Starch-based hydrogels can serve as effective carriers for pharmaceutical compounds such as drugs and proteins to develop drug-loaded hydrogel systems, providing controlled release over an extended period. The porous structure of a hydrogel allows for the diffusion of drugs, ensuring sustained and localized delivery to the target site. Moreover, starch-based hydrogels have been used as a powerful option in various biomedical fields, including cancer and infectious disease treatment. In addition, starch-based hydrogels have shown promise in tissue engineering applications since hydrogels can be used as scaffolds or matrices to support cell growth and tissue regeneration. Depending on techniques such as chemical crosslinking or physical gelation, it can create a three-dimensional network structure that tunes its mechanical properties and mimics the extracellular matrix. Starch-based hydrogels can also provide a supportive environment for cell attachment, proliferation, and differentiation to promote specific cellular responses and tissue regeneration processes with the loading of growth factors, cytokines, or other bioactive molecules. In this review, starch-based hydrogels as a versatile platform for various biomedical applications are discussed.